Automatic Generation Control in Multi Area Interconnected Power System by using HVDC Links - Yogendra Arya; Narendra Kumar; Hitesh Dutt Mathur (Institute of Advanced Engineering and Science, 2012)
This paper investigates the effects of HVDC link in parallel with HVAC link on automatic generation control (AGC) problem for a multi-area power system taking into consideration system parameter variations. A fuzzy logic controller is proposed for four area power system interconnected via parallel HVAC/HVDC transmission link which is also referred as asynchronous tie-lines. The linear model of HVAC/HVDC link is developed and the system responses to sudden load change are studied. The simulation studies are carried out for a four area interconnected thermal power system. Suitable solution for automatic generation control problem of four area electrical power system is obtained by means of improving the dynamic performance of power system under study. Robustness of controller is also checked by varying parameters. Simulation results indicate that the scheme works well. The dynamic analyses have been done with and without HVDC link using fuzzy logic controller in Matlab-Simulink. Further a comparison between the two is presented and it has been shown that the performance of the proposed scheme is superior in terms of overshoot and settling time.DOI: http://dx.doi.org/10.11591/ijpeds.v2i1.182